NEFT VA GAZ SANOATIDAGI APPARATLARNI KIMYOVIY KORROZIYADAN HIMOYALASH. VA ULARNI KIMYOVIY KARROZIYADAN SAQLASH YO‘LLARI - Abdukarimov , Mirzohid; Sharopov , Husanjon (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
The article provides information on corrosion problems observed in equipment and equipment at oil and gas facilities, as well as the application of correct solutions to these problems and protection depending on the type of metal in industries and enterprises, economic losses caused by corrosion in enterprises. concepts of avoidance are given.